Assessment of Vitamin E and Selenium as a Nutritional Intervention for Control of Subclinical Mastitis in Buffaloes at Farmer’s Field - , P.P. Singh; , Gaurav Jain; Aslam,; , Prem Singh Verma (Archives of Current Research International, 2025)
Aims: On Farm Trial (OFT) was conducted on graded Murrah buffaloes for assessment of effect of Vitamin E and Selenium as a nutritional intervention for control of subclinical mastitis (SCM) in Morena district of M.P. Place and Duration of Study: The study was conducted in two villages of Morena district of M.P. during the year 2021-22 and 2022-23. Methodology: For OFTs, 20 farmers having advanced pregnant buffaloes with previous history of mastitis were selected from group meeting. The selected farmers were divided randomly in two groups. First group of 10 farmers was designated as Farmers practice group (T1) which reared the buffaloes without any supplementation, second group of farmers was designated as supplemented animals group (T2) which reared the buffaloes with feeding supplement of vitamin E and Selenium powder @10 gram (containing 1000 IU Vitamin E and 10 mg Selenium) from twenty days prepartum to 20 days postpartum during two successive years 2021-22 and 2022-23. Results: In supplemented animals group (T2) a smaller number of animals were found suffering from subclinical mastitis in comparison to farmers practice group (T1) during both the year 2021-22 and 2022-23. The milk yield (liter/buffalo/2 month), net return and B:C ratios in supplemented animals group (T2) was higher in comparison to farmers practice group (T1) during both the year 2021-22 and 2022-23. Conclusion: The result of the trial successfully documented the positive effect of nutritional intervention of supplementation of vitamin E and Selenium for prevention of subclinical mastitis in graded Murrah buffaloes at farmer’s field.